2016
DOI: 10.1002/anie.201511491
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Glc1Man9‐Glycoprotein Probes by a Misfolding/Enzymatic Glucosylation/Misfolding Sequence

Abstract: Glycoproteins in non-native conformations are often toxic to cells and may cause diseases, thus the quality control (QC) system eliminates these unwanted species. Lectin chaperone calreticulin and glucosidase II, both of which recognize the Glc1 Man9 oligosaccharide on glycoproteins, are important components of the glycoprotein QC system. Reported herein is the preparation of Glc1 Man9 -glycoproteins in both native and non-native conformations by using the following sequence: misfolding of chemically synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
17
0
1
Order By: Relevance
“…Having concluded that UGGT's promiscuity is not dependent on the flexible linker between the catalytic domain and the N-terminal misfold sensing region, but is likely underpinned by the motions uncovered by the MD simulations, the question remains regarding UGGT's reported ability to survey not only folding of small-and medium-size glycoprotein monomers, but also quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes [23] [24] [25]. The Indeed, the MD conformational landscape observed in this work reaches extremely compact conformations, which may explain the activity of the enzyme against synthetic glycopeptides [16][17][18][19][20]. Importantly, monomeric UGGT can recognize and re-glucosylate a misfolded glycoprotein only if it can bridge the distance between a folding defect and at least one of the glycoprotein's N-linked glycosylation sites.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Having concluded that UGGT's promiscuity is not dependent on the flexible linker between the catalytic domain and the N-terminal misfold sensing region, but is likely underpinned by the motions uncovered by the MD simulations, the question remains regarding UGGT's reported ability to survey not only folding of small-and medium-size glycoprotein monomers, but also quaternary structure of glycoprotein oligomers and larger multi-glycoprotein complexes [23] [24] [25]. The Indeed, the MD conformational landscape observed in this work reaches extremely compact conformations, which may explain the activity of the enzyme against synthetic glycopeptides [16][17][18][19][20]. Importantly, monomeric UGGT can recognize and re-glucosylate a misfolded glycoprotein only if it can bridge the distance between a folding defect and at least one of the glycoprotein's N-linked glycosylation sites.…”
Section: Discussionmentioning
confidence: 94%
“…Since the discovery of UGGT back in 1989 [11,12], activity studies have used a range of glycoprotein substrates, such as urea-misfolded bovine thyroglobulin [11], mutants of exo-(1,3)-β-glucanase [13], RNase BS [14,15], small size synthetic compounds bearing high-mannose glycans attached to fluorescent aglycon moieties such as 'TAMRA' and 'BODIPY' [16,17] and chemically synthesized misfolded glycoproteins [18][19][20], to mention only a few. Although a comprehensive list of physiological UGGT substrate glycoproteins has not been compiled, and the molecular detail on UGGT:substrate interactions remains uncharacterized, it is apparent that the enzyme is highly promiscuous.…”
Section: Discussionmentioning
confidence: 99%
“…Die aktuelle Forschung in Kajiharas Gruppe dreht sich um die Synthese von Glykoproteinen mit homogenen Human‐N‐Glykanen und die Aufklärung der Glykanfunktionen. Er publizierte ein Full Paper über die chemische N‐terminale Modifizierung ungeschützter Peptide in Chemistry—A European Journal und eine Zuschrift über die Synthese von Glc 1 Man 9 ‐Glykoprotein‐Sonden in der Angewandten Chemie …”
Section: Ausgezeichnet …unclassified
“…Protein chemical synthesis and modification are important approaches for the generation of chemical probes to study the function of proteins and develop therapeutic biologics . However, owing to the presence of diversely functionalized amino acid side chains in a peptide/protein sequence, the development of effective chemical methods to directly manipulate these biomacromolecules is challenging.…”
Section: Figurementioning
confidence: 99%